2019
DOI: 10.3390/su11184917
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Trust Influencing Mechanism of Robo-Advisor Service: A Mixed Method Approach

Abstract: As a typical application of fintech, the robo-advisor has increasingly gained attention over the last decade. However, most research regarding the robo-advisor has focused on its development issues such as performance improvement and regulation, while limited research has paid attention to trust. This research extends the literature by investigating the trust influencing mechanism of robo-advisors by a mixed method approach. Specifically, we identified six salient trust influencing factors by qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 96 publications
2
30
0
Order By: Relevance
“…This finding suggests that investment experience lowers the barriers to acceptance of this new technology; thus, experienced customers, who will be less troubled by technology threats, may be a good target sector for robo-advisors. This finding is in line with previous research that found that consumers must have confidence in both the vendor (firm) and the technology to adopt new technology-based services (Belanche et al , 2014) such as robo-advisors (Cheng et al , 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that investment experience lowers the barriers to acceptance of this new technology; thus, experienced customers, who will be less troubled by technology threats, may be a good target sector for robo-advisors. This finding is in line with previous research that found that consumers must have confidence in both the vendor (firm) and the technology to adopt new technology-based services (Belanche et al , 2014) such as robo-advisors (Cheng et al , 2019).…”
Section: Discussionsupporting
confidence: 91%
“…e mining of financial data is to promote the development of financial economy. e content of data mining includes things and dimensions, distribution and relationships, description and prediction, and phenomena and knowledge [21]. e main techniques of data mining include forecasting, clustering, association rules, and time series analysis.…”
Section: Data Mining Technology and Data Storage Technologymentioning
confidence: 99%
“…This may have yielded slightly more positive perceptions of current EU legitimacy (HDM condition) as compared to the German population, as previous evidence suggests that higher levels of education are associated with more positive attitudes to the EU (Boomgaarden et al, 2011). Furthermore, the sample may be over-sophisticated in terms of digital literacy and general interest in ADM, which are likely to be associated with perceived legitimacy of as well as trust in algorithmic processes (Cheng et al, 2019). To make stronger claims in terms of the generalizability of the results, future research should use representative national samples.…”
Section: Implications For Future Empirical Researchmentioning
confidence: 88%